2017
DOI: 10.1371/journal.pone.0187527
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic structure of the Common hamster (Cricetus cricetus L.): Late Pleistocene connections between Caucasus and Western European populations

Abstract: The Common hamster (Cricetus cricetus) is one of the most endangered mammals in Western and Central Europe. Its genetic diversity in Russia and Kazakhstan was investigated for the first time. The analysis of sequences of an mtDNA control region and cytochrome b gene revealed at least three phylogenetic lineages. Most of the species range (approximately 3 million km2), including central Russia, Crimea, the Ural region, and northern Kazakhstan), is inhabited by a single, well-supported phylogroup, E0. Phylogroup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
41
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 41 publications
5
41
0
Order By: Relevance
“…the analysis of whole mtDNA genome could lead to new and important inferences about the origin and diversification of S. scrofa populations. A similar trend involving the proximity of Caucasian and Mediterranean haplotypes has also been reported for common hamster (Cricetus cricetus), byFeoktistova et al (2017). The results of our study revealed the peculiar haplotype composition of the wild boar inhabiting two specific areas: East-Caucasus (Dagestan) and Central Italy.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…the analysis of whole mtDNA genome could lead to new and important inferences about the origin and diversification of S. scrofa populations. A similar trend involving the proximity of Caucasian and Mediterranean haplotypes has also been reported for common hamster (Cricetus cricetus), byFeoktistova et al (2017). The results of our study revealed the peculiar haplotype composition of the wild boar inhabiting two specific areas: East-Caucasus (Dagestan) and Central Italy.…”
supporting
confidence: 88%
“…Most interesting was the similarity of Central Italian and Caucasian haplotypes (as shown by TreeMix analysis,Figure 5). A similar trend involving the proximity of Caucasian and Mediterranean haplotypes has also been reported for common hamster (Cricetus cricetus), byFeoktistova et al (2017). This could explain the presence of two genetic lineages in the territory of modern Italy, as shown by a number of previous studies(Larson et al, 2005;Scandura et al, 2008).…”
supporting
confidence: 78%
“…In our study concerning phylogeography of the Common hamster in Russia and Kazakhstan (Feoktistova et al, 2017) we discovered the single E1 haplotype in Bryansk province in Western Russia. Whereas more eastern territories of Western Russia, Volga region, Ural, and Northern Kazakhstan are populated by hamsters of another mitochondrial phylogroup, we named E0.…”
Section: поволжский экологический журнал № 4 2018mentioning
confidence: 81%
“…As markers of phylogenetic lineages, we used sequences of mitochondrial control region and cytochrome b (cytb) gene. DNA extraction and amplification were done according to the method described earlier (Feoktistova et al, 2017). The sequences were obtained using the BigDye Terminator v. 3.1 kit and sequencing on a Genetic Analyzer 3500 (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…campbelli within the last pair had been considered disputable until evidence of reproductive isolation was obtained (Sokolov & Vasilieva, ). The distance between morphologically distinct subspecies M. raddei avaricus and M. r. nigriculus was estimated at 2.3% (Neumann et al., ), while that between the two most divergent lineages (subspecies) of Cricetus cricetus was close to 1.5% (Neumann et al., ; Feoktistova et al., ). Important exceptions to the former cases are presented by Allocricetulus , where the distance between chromosomally distinct species A. eversmanni and A. curtatus is just 2% (GenBank: , , ), and by Anatolian populations of M. brandti , in which haplotypes differing at up to 9% were found to co‐occur (Neumann et al., ); however, both these situations require additional examination.…”
Section: Discussionmentioning
confidence: 99%